ANALYSING THE PERFORMANCE OF EDFA AND APD RECEIVER IN DYNAMIC WDN NETWORK - Joel, Nikita M; A, Brintha Therese (Asian Journal of Pharmaceutical and Clinical Research, 2017)
This paper demonstrates the performance of Erbium doped fiber amplifier(EDFA) and APD receiver in a dynamic wavelength division multiplexing(WDM) system. A four channel 10Gb/s system is taken into consideration and the performance of Erbium doped fiber Amplifier is assessed. The experimental setup consists of a transmitter, a receiver and two intermediate nodes. The transmitted system is tested for Bit Error Rate (BER) and Eye pattern at the receiver. The spectrum is also analysed for different length of fiber. Add Drop Experiment was carried on in which a laser source was switched on and off continuously to assess the transient response of WDM system. Then the Eye Pattern is analysed in which Erbium doped fiber Amplifier system will provide a clear open eye with no degradation of signal.